2010
DOI: 10.1130/b30085.1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of crustal anatexis to the tectonic evolution of Indian crust beneath southern Tibet

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
95
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 88 publications
8
95
0
4
Order By: Relevance
“…Previous studies on the timing of crustal anatexis in the Himalayan orogenic belt indicated that leucogranites formed at 27-10 Ma in the NHGD and the HHCS are typical S-type granites, derived from muscovite dehydration melting of metapelites and characterized by high initial 87 Sr/ 86 Sr ratios of 0.7300-0.7800 and low  Nd from 10 to 15 [1][2][3][4][5][6][7]16,46,47]. Experimental results [6,7], theoretic calculations [22,23] and field investigations [4,16,18] all suggest that fertile metapelites could undergo progressive partial melting with variations in temperature, pressure, and water content, which leads to the formation of granites with different geochemical characteristics in major and trace element as well as in isotope (e.g.…”
Section: Source Rock Of the Paiku Composite Leucogranitementioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on the timing of crustal anatexis in the Himalayan orogenic belt indicated that leucogranites formed at 27-10 Ma in the NHGD and the HHCS are typical S-type granites, derived from muscovite dehydration melting of metapelites and characterized by high initial 87 Sr/ 86 Sr ratios of 0.7300-0.7800 and low  Nd from 10 to 15 [1][2][3][4][5][6][7]16,46,47]. Experimental results [6,7], theoretic calculations [22,23] and field investigations [4,16,18] all suggest that fertile metapelites could undergo progressive partial melting with variations in temperature, pressure, and water content, which leads to the formation of granites with different geochemical characteristics in major and trace element as well as in isotope (e.g.…”
Section: Source Rock Of the Paiku Composite Leucogranitementioning
confidence: 99%
“…Granites, migmatites, and high-grade metamorphic rocks are important components within these two belts and record distinct types of metamorphism and partial melting reactions of middle-lower crustal materials in response to the tectonic evolution of the Himalayan orogen [1,4,8,13,14,16,[26][27][28][29]. NHGD within the Tethyan Himalaya consists of a series of semi-continuous oval shape gneiss dome.…”
Section: Geological Setting and Sample Descriptionsmentioning
confidence: 99%
See 3 more Smart Citations